Development of student worksheets green chemistry oriented to train creative thinking skills on reaction rate topic - Amelia Wulandari; Mitarlis Mitarlis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to produce student worksheets with green chemistry oriented to train creative thinking skills in matter with reaction rate proper. The green chemistry principles studied in this research are limited to 1, 5, and 12. The research development method uses a 4-D model (define, design, develop, and disseminate) and is limited to the development stage. Limited trials were conducted on 35 students in class XI IPA 1 senior high school. The development of student worksheets is feasible if it fulfills three aspects, including aspects of validity, practicality, and effectiveness. It is declared valid if it gets a minimum mode value of 3 from the range of values ​​1-5 and is declared practical and effective if the proportion results are ≥ 61%. The results of the development of student worksheets mean that the feasibility of student worksheets in terms of theoretical validity consists of several things, namely content criteria that obtain a mode value of 5, linguistic criteria obtain a mode value of 5, presentation features obtain a mode value of 5, graphical criteria obtain a mode value 4, green chemistry scoring gets a mode value of 5, and criteria for creative thinking skills gets a mode value of 5. The practicality of student worksheets is seen from the student response questionnaire, which is supported by observations of student activities and the implementation of learning, each of which obtains very practical results with an average proportion of 94.64%, 94.5%, and 98.21%. The aspect of effectiveness is viewed from the results of the creative thinking ability test, which obtained 0.85, which is in the high category. Based on the results of validity, practicality, and effectiveness, it can be interpreted that the student worksheets developed are declared feasible for use in the teaching and learning process.